Colloidal silver-based lateral flow immunoassay for detection of profenofos pesticide residue in vegetables. Issue 21 (29th April 2022) - Wu, Kuo-Hui; Huang, Wen-Chien; Chang, Shu-Chen; Shyu, Rong-Hwa
Abstract : A colloidal silver nanoparticle (AgNP)-based lateral flow immunoassay (LFIA) was evaluated in terms of the rapid detection of profenofos (PEO) pesticide residue in vegetables. Abstract : A colloidal silver nanoparticle (AgNP)-based lateral flow immunoassay (LFIA) was evaluated in terms of the rapid detection of profenofos (PEO) pesticide residue in vegetables. Colloidal AgNPs, of a diameter of approximately 20 nm, were surface-modified with trisodium citrate dehydrate (TSC) in order to improve their stability and dispersion. An anti-profenofos polyclonal antibody (pAb) was successfully immobilized on the surface of the AgNPs by ionic interaction and characterized using UV-vis, SEM, TEM, FTIR and XPS analyses. Surface modification of Ag–pAb conjugates of varying pH, pAb content and cross-reactivity was employed to design and prepare labels for use in an LFIA to examine whether these factors affect the performance of the assay. The visible detection limit and optical detection limit of the PEO test strip were 0.20 and 0.01 ppm, respectively, in PEO standard solution. This assay showed no cross-reaction with omethoate, methamidophos or pyraclofos. Finally, the PEO test strip was effectively applied for the detection of PEO in liquid vegetables A and B, with optical detection limits of 0.09 and 0.075 ppm, respectively.